Long-Lasting Activity of ERK Kinase Depends on NFATc1 Induction and Is Involved in Cell Migration-Fusion in Murine Macrophages RAW264.7 - Russo, Roberta (Int J Mol Sci, 2020)
Macrophages are mononuclear cells that become osteoclasts (OCs) in the presence of two cytokines, macrophage colony-stimulating factor (M-CSF), and receptor activator of NF-κB ligand (RANKL). RANKL binding to its specific receptor RANK leads to OCs differentiation mainly by nuclear factor of activated T-cells cytoplasmic 1 (NFATc1). In our previous study, the analysis of the protein network in NFATc1-knockdown cells, using the Ingenuity Pathway Analysis (IPA), showed a link between NFATc1 and Mitogen-activated protein kinase kinase (MEK)-extracellular receptor kinase (ERK) signaling pathway. Therefore, this study aimed to extend our knowledge of the relationship between NFATc1 and the ERK. Here, we demonstrate that delayed ERK1/2 phosphorylation in pre-OC RANKL-induced depends on NFATc1. Indeed, the knockdown of NFATc1 reduced the phosphorylation of ERK1/2 (60%) and the pharmacological inhibition of the ERK1/2 kinase activity impairs the expression of NFATc1 without preventing its translocation into the nucleus. Furthermore, silencing of NFATc1 significantly reduced RANKL-induced migration (p < 0.01), and most pre-OCs are still mononuclear after 48 h (80 ± 5%), despite the presence of actin rings. On the other hand, the inhibitors FR180204 and PD98059 significantly reduced RANKL-induced cell migration (p < 0.01), leading to a reduction in the number of multinucleated cells. Finally, we suggest that long-lasting ERK activity depends on NFATc1 induction and is likely linked to cell migration, fusion, and OC differentiation.